СЛИВКО ЄВГЕНІЯ МАРТИНІВНА (до 60-річчя від дня народження) - Матковський, О.; Наумко, І.; Павлунь, М.; Волошин, П.; Скакун, Л.; Білоніжка, П.; Гулій, В. (Мінералогічний збірник, 2024)
СЛИВКО ЄВГЕНІЯ МАРТИНІВНА (до 60-річчя від дня народження)